A hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel and preparation method thereof
Through electrostatic cross-linking, an injectable hydrogel with electrostatic assembly of hyaluronic acid-tripeptide molecules was prepared, which solved the problems of poor mechanical strength and complicated chemical modification of traditional hyaluronic acid solutions, and achieved shear thinning, rapid self-repair and good mechanical stability of the hydrogel, which was suitable for applications in the pharmaceutical field.
Patent Information
- Application Number
- CN202410788058.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-18
AI Technical Summary
Traditional hyaluronic acid solutions have poor mechanical strength in medical fields such as surgical filling, which is easy to degrade and diffuse, resulting in unsatisfactory results, and the chemical modification methods are cumbersome and may bring physiological toxicity.
By utilizing the electrostatic crosslinking between negatively charged hyaluronate and positively charged tripeptide molecules under physiological conditions, an electrostatic co-assembled injectable hydrogel with good injectability and mechanical stability was prepared.
It realizes shear thinning and fast self-repairing properties of hydrogels, has good injectable properties and mechanical stability, does not require chemical modification, and is gentle in process conditions, which is suitable for large-scale industrial production.
Smart Images

Figure CN118717653B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel and a preparation method thereof. Background Art
[0002] Hyaluronic acid, also known as hyaluronic acid, is widely present in organisms and tissues. It is a disaccharide unit glycosaminoglycan composed of D-glucuronic acid and N-acetylglucosamine. It has high viscoelasticity and unique physical and chemical properties such as lubrication and moisturizing. Sodium hyaluronate has been used clinically as a viscoelastic agent in ophthalmic and orthopedic surgery, and can also be used to prevent postoperative adhesion. Clinical applications have shown that hyaluronic acid has good biocompatibility, but traditional hyaluronic acid solutions have the disadvantages of poor mechanical strength and easy degradation and diffusion in tissues, so the effects in medical fields such as surgical filling are not ideal.
[0003] In recent years, injectable hydrogels, as a new form of drug, have good mechanical stability. They can be easily injected into the lesion site in the body through medical endoscopes or minimally invasive surgery, which can minimize the trauma and pain of patients, achieve rapid local administration, promote the enrichment of drugs at the lesion site, and reduce the toxic side effects on normal tissues. They have broad application prospects in surgical fillers, drug loading and sustained release, cell scaffolds or tumor treatment. In recent years, researchers have conducted a large number of structural modification and modification studies on hyaluronic acid. Through esterification, amidation and reductive amination reactions, hyaluronic acid is cross-linked, hydrophobic, grafted and ring-opened, thereby obtaining hyaluronic acid-based gels with certain functionality (Hyaluronic Acid in Biomedical Fields: New Trends from Chemistry to Biomaterial Applications, Antonia Di Mola et al., Int. J. Mol. Sci. 2022, 23, 14372). However, the cumbersome chemical modification is not only not conducive to the large-scale industrial production of hyaluronic acid-based gels, but the modified hyaluronic acid and residual modified groups may cause potential physiological toxicity to the human body. In addition, the reversibility of chemical cross-linking is poor, making it difficult to form a good injectable hydrogel.
[0004] Therefore, developing a hyaluronic acid injectable hydrogel that has good injectability and mechanical stability by direct physical method without any chemical modification of hyaluronic acid has very important application prospects and value. Summary of the invention
[0005] Based on the above-mentioned defects of the prior art, the present invention provides a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel with shear thinning, rapid self-repair and good biocompatibility and a preparation method thereof based on the electrostatic cross-linking effect between negatively charged hyaluronate and positively charged tripeptide molecules under physiological conditions. The preparation method is simple and the required conditions are mild, and it is easy for large-scale industrial production.
[0006] To achieve the above-mentioned purpose, the present invention provides a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel, wherein the hydrogel is composed of hyaluronic acid with negatively charged molecular chains, tripeptide molecules with positively charged molecules, and a buffer solution; wherein the tripeptide molecule is a FYK tripeptide with a sequence of phenylalanine (F)-tyrosine (Y)-lysine (K).
[0007] Preferably, the hyaluronate is selected from one or more of sodium hyaluronate, potassium hyaluronate and zinc hyaluronate.
[0008] Preferably, the molecular weight of the hyaluronate is 400,000-1.5 million.
[0009] Preferably, the mass percentage of the hyaluronate in the buffer solution is 1.0wt%-3.0wt%.
[0010] Preferably, the molar concentration of the tripeptide molecule in the buffer is 10-100 mmol / L.
[0011] Preferably, the buffer solution is selected from one or more of a phosphate buffer solution, a citrate buffer solution, and a borate buffer solution.
[0012] Preferably, the pH value of the buffer solution is 5.0-8.0.
[0013] The present invention further provides a method for preparing the above-mentioned injectable hydrogel, comprising the following steps: mixing hyaluronate and tripeptide molecules in a buffer solution and standing at room temperature to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
[0014] The beneficial effects of the present invention are:
[0015] 1. The hyaluronic acid-tripeptide molecule electrostatic co-assembly injectable hydrogel provided by the present invention is composed of hyaluronate with negatively charged molecular chains, tripeptide molecules with positively charged molecules, and buffer. Wherein, the hyaluronate with negatively charged molecular chains and the tripeptide molecules with positively charged molecules form a three-dimensional network of hydrogel in the aqueous solution system through electrostatic crosslinking. When it is transferred to the syringe and shear force is applied, the electrostatic crosslinking in the gel network is destroyed, so that the system exhibits shear-thinning characteristics, which is conducive to the gel being squeezed to the target position. Subsequently, thanks to the reversibility of the electrostatic effect between the molecular chains, electrostatic crosslinking occurs again between the extruded hydrogel molecular chains, so that the hydrogel exhibits the characteristics of rapid self-repair. In summary, the hydrogel provided by the present invention has the performance of "shear thinning" and "rapid self-repair" at the same time, can show good injectable performance, and because it itself also has good mechanical stability, therefore, the injectable hydrogel provided by the present invention has both good mechanical stability and injectable performance, which can provide great convenience and excellent effect in the application under endoscopy or minimally invasive surgery.
[0016] 2. The injectable hydrogel provided by the present invention does not require additional chemical modification of hyaluronic acid. It only utilizes the electrostatic cross-linking effect between negatively charged hyaluronate and positively charged KYF tripeptide molecules under physiological conditions to achieve the preparation of the above-mentioned hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel. As a physical cross-linking method, no chemical cross-linking agent is required and no other reaction intermediates are generated during the cross-linking process. The process conditions are mild and it is easy to carry out large-scale industrial production. It has a very broad application prospect in the field of biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the structure and principle of the injectable hydrogel in Example 1;
[0018] Figure 2 is an inverted photograph of the injectable hydrogel prepared in Example 1;
[0019] Figure 3 This is a microscopic morphology of the injectable hydrogel prepared in Example 1;
[0020] Figure 4 The rheological frequency sweep test results of the injectable hydrogel prepared in Example 2;
[0021] Figure 5 The rheological amplitude scanning test results of the injectable hydrogel prepared in Example 2;
[0022] Figure 6 The biosafety test results of the injectable hydrogel prepared in Example 2;
[0023] Figure 7 The shear thinning performance test results of the injectable hydrogel prepared in Example 3;
[0024] Figure 8 The rapid self-healing performance test results of the injectable hydrogel prepared in Example 3;
[0025] Fig. 9 This is a photo of the injection effect of the injectable hydrogel prepared in Example 3;
[0026] Fig.10 This is an inverted photograph of the hyaluronic acid solution system prepared in Comparative Example 1;
[0027] Fig.11 This is an inverted photograph of the tripeptide molecular solution system prepared in Comparative Example 2;
[0028] Fig.12 This is an inverted photograph of the hyaluronic acid-tripeptide molecule prepared in Comparative Example 3. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel, which is composed of 0.03g potassium hyaluronate with a molecular weight of 1-1.5 million, 4.57mg FYK tripeptide molecule, and 1mL pH 5.0 citrate buffer.
[0032] The preparation method of the above-mentioned injectable hydrogel comprises the following steps: weighing 0.03 g of potassium hyaluronate with a molecular weight of 1 million to 1.5 million and 4.57 mg of FYK tripeptide molecules, mixing them in 1 mL of pH 5.0 citrate buffer, vortexing, ultrasonicating and heating in a water bath to completely dissolve them, and letting them stand overnight to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
[0033] Among them, potassium hyaluronate was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number Y56867-1g; citrate buffer was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the item number C301550-250ml; FYK tripeptide molecule was customized from Jier Biochemical Co., Ltd. with the item number 815079.
[0034] The structure and principle of the injectable hydrogel are as follows Figure 1 As shown, based on the electrostatic self-assembly of positively charged FYK tripeptide molecules and negatively charged potassium hyaluronate in citrate buffer, a hydrogel with a three-dimensional network structure is formed. When a shear force is applied to it, the gel becomes a dilute solution and is squeezed out by a syringe. When the shear force disappears, the dilute solution returns to a hydrogel state, thereby achieving the injectable performance of the hydrogel.
[0035] After the injection of hydrogel in the glass bottle inverted, Figure 2 As shown, no flow state occurs, indicating that it has returned to the hydrogel state.
[0036] Scanning electron microscopy was further used to characterize the microscopic morphology of the injectable hydrogel. Figure 3 As shown, the hydrogel generally presents a loose porous structure of hydrogel, and obvious fibrous substances can be seen locally at the edge, which indicates that the hydrogel first forms fibers through electrostatic self-assembly, and then forms an injectable hydrogel through assembly between fibers.
[0037] Example 2
[0038] This embodiment provides a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel, which is composed of 0.04g hyaluronic acid zinc with a molecular weight of 800,000-1,000,000, 45.7mg FYK tripeptide molecule, and 2mL pH 8.0 borate buffer.
[0039] The preparation method of the above-mentioned injectable hydrogel comprises the following steps: weighing 0.04 g of zinc hyaluronate with a molecular weight of 800,000-1,000,000 and 45.7 mg of FYK tripeptide molecules and mixing them in 2 mL of borate buffer with a pH of 8.0, then completely dissolving them by vortexing, ultrasound and water bath heating, and standing overnight to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
[0040] Among them, zinc hyaluronate was purchased from Wuhan Kmik Biotechnology Co., Ltd. with the item number PC20230115; borate buffer was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the item number B407179-500mL; FYK tripeptide molecule was customized from Jier Biochemical Co., Ltd. with the item number 815079.
[0041] The rheological properties of the injectable hydrogel were characterized using an Anton Paar MCR 302 rotational rheometer (reference Dipeptide Self-assembled Hydrogels with Shear-Thinning and Instantaneous Self-healing Properties Determined by Peptide Sequences. ACS Appl. Mater. Interfaces 2020, 12 (19), 21433-21440.) The test temperature was set at 25 °C. The results are shown in Figure 4 and 5 As shown, the storage modulus of the injectable hydrogel of this embodiment is always greater than the loss modulus under the shear strain of 0.001%-1.3% and the shear frequency of 0.1-39.8 Hz, which indicates that the solid hydrogel is formed by electrostatic cross-linking.
[0042] The cytotoxicity of the injectable hydrogel of this embodiment was tested with reference to the relevant provisions of GB / T 16886.5-2017 Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test. The results are shown in Figure 6 The results show that the injectable hydrogel of the present invention has substantially no cytotoxicity, has good biocompatibility, and is conducive to in vivo application.
[0043] Example 3
[0044] This embodiment provides a hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel, which is composed of 0.03g of sodium hyaluronate with a molecular weight of 400,000-800,000, 137.1mg of FYK tripeptide molecule, and 3mL of phosphate buffer with a pH of 7.4.
[0045] The preparation method of the above-mentioned injectable hydrogel comprises the following steps: weighing 0.03g of sodium hyaluronate with a molecular weight of 400,000-800,000 and 137.1mg of FYK tripeptide molecules and mixing them in 3mL of phosphate buffer with a pH of 7.4, then completely dissolving them by vortexing, ultrasound and water bath heating, and standing overnight to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
[0046] Among them, sodium hyaluronate was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number S12034-25g; phosphate buffer was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number R26022-500mL; FYK tripeptide molecule was customized from Jier Biochemical Co., Ltd. with the item number 815079.
[0047] The injectable properties of the injectable hydrogel of this embodiment were characterized using Anton Paar MCR 302 rotational rheometer (reference Dipeptide Self-assembled Hydrogels with Shear-Thinning and Instantaneous Self-healing Properties Determined by Peptide Sequences. ACS Appl. Mater. Interfaces 2020, 12 (19), 21433-21440.), and the test temperature was set to 25 ° C. The results are as follows Figure 7 As described above, the viscosity of the injectable hydrogel in this example gradually decreases with the increase of shear rate, which indicates that it has the property of shear thinning. When the shear strain applied to the hydrogel is reduced from 10% to 0.01%, the results are as follows: Figure 8 As shown in the figure, the storage modulus and loss modulus of the hydrogel are rapidly reversed within 10 seconds, that is, it quickly changes from a fluid under high shear to a gel under low shear, which shows that the injectable hydrogel has a rapid shear self-repair function. Thanks to the good shear thinning and rapid self-repair properties, the system has good injectability. The injection effect is as follows Fig. 9 shown.
[0048] Comparative Example 1
[0049] This comparative example provides a hyaluronic acid hydrogel system, which differs from Example 3 only in that it does not contain positively charged KYF tripeptide molecules. The specific preparation method comprises the following steps:
[0050] 0.03 g of sodium hyaluronate with a molecular weight of 400,000-800,000 is weighed and dissolved in 3 mL of phosphate buffer with a pH of 7.4, and then completely dissolved by vortexing, ultrasound and water bath heating, and allowed to stand overnight to obtain the hyaluronic acid hydrogel system.
[0051] Among them, sodium hyaluronate was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number S12034-25g; phosphate buffer was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number R26022-500mL.
[0052] Fig.10 This is an inverted appearance diagram of the hydrogel system prepared in this comparative example. Since the positively charged KYF tripeptide molecules were not added to the system for electrostatic self-assembly with the negatively charged hyaluronic acid, the obtained gel system was still a clear flowing liquid after inversion. This shows that the tripeptide molecules with opposite charges are the key substances for preparing the hyaluronic acid-tripeptide molecule injectable hydrogel by electrostatic co-assembly.
[0053] Comparative Example 2
[0054] This comparative example provides a hydrogel system of KYF tripeptide molecules, which differs from Example 3 only in that it does not contain negatively charged hyaluronic acid molecules. The specific preparation method comprises the following steps:
[0055] 137.1 mg of FYK tripeptide molecules were weighed and mixed in 3 mL of phosphate buffer solution with a pH of 7.4, and then completely dissolved by vortexing, ultrasound and water bath heating, and then the hyaluronic acid hydrogel system was obtained.
[0056] Among them, the FYK tripeptide molecule was customized by Jier Biochemical Co., Ltd. with the item number 815079; the phosphate buffer was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number R26022-500mL.
[0057] Since negatively charged hyaluronic acid molecules are not added to the system, the resulting gel system is in a gel state initially. Subsequently, due to the crystallization of the tripeptide molecules, the gel network is destroyed, thereby transforming it into a flowing liquid. Fig.11 This is an inverted appearance of the hydrogel system prepared in this comparative example, which is a white turbid flowing liquid after being left to stand overnight. This shows that hyaluronic acid molecules with opposite charges are also the key substances for preparing hyaluronic acid-tripeptide molecule injectable hydrogels through electrostatic co-assembly.
[0058] Comparative Example 3
[0059] This comparative example provides a hyaluronic acid-tripeptide molecule hydrogel system, which is composed of 0.03g sodium hyaluronate with a molecular weight of 400,000-800,000, 137.1mg FYL tripeptide molecule, and 3mL phosphate buffer with a pH of 7.4. The difference between this system and Example 3 is that FYL is a negatively charged tripeptide molecule.
[0060] The preparation method of the above system comprises the following steps: weighing 0.03 g of sodium hyaluronate with a molecular weight of 400,000-800,000 and 137.1 mg of FYL tripeptide molecules and mixing them in 3 mL of phosphate buffer with a pH of 7.4, then completely dissolving them by vortexing, ultrasound and water bath heating, and standing overnight to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
[0061] Among them, sodium hyaluronate was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number S12034-25g; phosphate buffer was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with the item number R26022-500mL; FYL tripeptide molecule was purchased from Hangzhou Zhuanpeptide Biotechnology Co., Ltd. with the item number 133918.
[0062] like Fig.12As shown, the obtained gel system is white and opaque, and flows easily after inversion, which means that no hydrogel is formed. This is because hyaluronic acid itself has a negative charge, and the FYL tripeptide molecule itself is also negatively charged, so it is difficult to construct a three-dimensional gel network structure through electrostatic self-assembly, and thus a hydrogel cannot be formed. This shows that the structure of the tripeptide molecule is not arbitrarily replaceable.
[0063] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel, characterized in that: The hydrogel is composed of hyaluronate with negatively charged molecular chains, tripeptide molecules with positively charged molecules, and a buffer; wherein the tripeptide molecules have a sequence of phenylalanine-tyrosine-lysine; The molecular weight of the hyaluronate is 400,000-1.5 million; the mass percentage of the hyaluronate in the buffer solution is 1.0wt%-3.0wt%; the molar concentration of the tripeptide molecule in the buffer solution is 10-100mmol / L.
2. The hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel according to claim 1, characterized in that: The hyaluronate is selected from one or more of sodium hyaluronate, potassium hyaluronate and zinc hyaluronate.
3. The hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel according to claim 1, characterized in that: The buffer solution is selected from one or more of a phosphate buffer solution, a citrate buffer solution, and a borate buffer solution.
4. The hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel according to claim 1, characterized in that: The pH value of the buffer solution is 5.0-8.
0.
5. A method for preparing the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel according to any one of claims 1 to 4, characterized in that: The following steps are involved: Hyaluronate and tripeptide molecules are mixed in a buffer solution and allowed to stand at room temperature to obtain the hyaluronic acid-tripeptide molecule electrostatic co-assembled injectable hydrogel.
Citation Information
Patent Citations
Hyaluronic acid hydrogels with prolonged antimicrobial activity
CN114040785A